2017
DOI: 10.2486/indhealth.2016-0021
|View full text |Cite
|
Sign up to set email alerts
|

Medical costs of asbestos-related diseases in Spain between 2004 and 2011

Abstract: The objective of this article was to estimate the medical costs derived from malignant ARD treatment in the Spanish National Health System (NHS) between 2004 and 2011. Estimation of direct healthcare costs was based on national primary data on the cost of specialized care for inpatients and outpatients treated at NHS hospitals and on national and regional secondary data on costs of primary healthcare and pharmaceutical prescriptions. A prevalence approach was used to estimate the overall burden of ARDs. Direct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 17 publications
1
4
0
1
Order By: Relevance
“…Several studies investigated the social burden of mesothelioma, someone focused on years of life lost and years of potential life lost 30 others (like this) on the hospitalisation cost. [31][32][33][34][35] Even if direct comparisons are not possible because of different economies and financial management of hospitals between countries, we have found very similar ratios between mean hospital costs by surgical procedures with a recent American work 35 (table 2).…”
Section: Discussionsupporting
confidence: 50%
“…Several studies investigated the social burden of mesothelioma, someone focused on years of life lost and years of potential life lost 30 others (like this) on the hospitalisation cost. [31][32][33][34][35] Even if direct comparisons are not possible because of different economies and financial management of hospitals between countries, we have found very similar ratios between mean hospital costs by surgical procedures with a recent American work 35 (table 2).…”
Section: Discussionsupporting
confidence: 50%
“…Another study reported that the poor completeness of recorded data hinders accurate knowledge of effects of asbestos on Spanish workers' health [21]. Thus, in Spain, the time trend and incidence rates related to occupational asbestosis might indicate that disease cases in that country are under-reported [7].…”
Section: Discussionmentioning
confidence: 99%
“…A study in a group of asbestosis-diagnosed patients, conducted on the basis of hospital discharge data from Italy (covering the period 2001-2015), the hospitalization rate for all asbestosis cases amounted to 25.2 per 1,000,000 inhabitants [6]. During 1963-2010, there were 815 asbestosis cases in Spain [7]; in Germany during 2013-2016, about 4,100 of all asbestos-related disease cases, which in total amounted to approximately 9,400 per year, represented cases of occupational disease [8]. In Poland, data on occupational diseases related to asbestos are collected by local sanitary inspectors and sent to the Nofer Institute of Occupational Medicine in Łódz, where they are kept in the Central Register of Occupational Diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, a set of year dummies, D t , has been included to capture technical change in (2) (z) = + rICU rICU , 2 We thank an anonymous referee for suggesting this alternative interpretation of the medical labour input. 3 From the pioneering work of [29], the WCU has been used both in different academic studies [30,31] 4 That is to say: r ICU = ICUdischarges Discharges ; where: Discharges = General Medicine + 1.5 Surgery + 1.3 Paediatric Medicine + 1.2 Obstetric Medicine 5 The dependent variable in the output distance function would be −lny 1 . Using lny 1 as the dependent variable, the sign of the estimated parameters changes allowing a more standard interpretation.…”
Section: Methodsmentioning
confidence: 99%
“… 3 From the pioneering work of [ 29 ], the WCU has been used both in different academic studies [ 30 , 31 ] and by the Spanish Ministry of Health, which uses it to calculate economic indicators such as budget or expenditure per activity (where hospital activity is weighted by WCU). The WCU takes into account the consumption of resources of each hospital activity, and with this information, weighs the different activities taking as reference a medical stay (that is to say, a medical stay = 1 WCU).…”
mentioning
confidence: 99%